Implementasi Nilai-Nilai Peduli Sosial Dan TanggungjawabPada Supeltas (Sukarelawan Pengatur Lalu Lintas) - ANDRISARI, FARIDA OKTAVIANI, Dra. Sundari,SH,M Hum (2016)
Value is the estimated, important properties that are considered important or useful for humanity that can encourage people to achieve its objectives. Social care is the attitude of connectedness with humanity in general, an empathy for each member of the human community. Therefore, social concern is interest or our interest to help others. Responsibility is man's consciousness of behavior or ctions are intentional or unintentional. Responsibility also means do as the embodiment awareness obligation. Responsibility is natural means has become part of human life burdened with responsibilities. Officers impromptu at the junction, intersection or crossings, help regulate traffic or ferrying pedestrians certainly quite helpful. Despite the existence is not without risk. Starting from ready to sunbathe, abused, unpaid, in the rain, to hit. Supelatas (the Traffic Volunteers) has now become a phenomenon in the city of Solo is very interesting to study. The phenomenon of the above results indicate that the clerk Supeltas help make the T-junction, an intersection, and the crossings are better organized so that there is no congestion. Action needs to be done to appreciate the performance of their sincerity is by paying attention as it should. The riders, had been due to give appropriate reward for the services they have given comfort. Keywords: Values of social care, responsibility and Supeltas (volunteer traffic controller)